Implementasi Pengelolaan Perpustakaan di Madrasah Swasta - Wawan Hermawan; Ari Prayoga (MANAZHIM, 2020)
The book collection has not been properly inventoried, student interest in reading visits is still low, supervision is carried out every 2/3 months, there is a loss of inventory of madrasa library books, the head of the library does not have staff resources. The purpose of this study is to uncover and analyze the management process including; planning, implementing, organizing, monitoring and evaluating libraries in Madrasah Aliyah Darussalam Sumedang, Indonesia. This research method is descriptive with a qualitative approach. Data collection techniques use; study interviews with the head of the library as the key informant and head of the madrasa, study documents include, book archives, library work programs, library visit books; Observation studies record library activity activities, discussion processes, weekly meetings. The results showed that; first, planning is carried out with the madrasa head at the madrasa level meeting by submitting a work program and submitting a draft budget (RAB); second, organizing is regulated based on the statement of the headmaster of madrasa no: MA.i / S / 20 / pp.006 / 001/2019 concerning the additional duties of Elyana Barbera as head of the library and does not yet have accompanying staff; third, the program implementation at the library is carried out by the head of the library, namely borrowing books, daily library services, work program socialization; fourth, supervision is carried out incidentally monthly and weekly, direct and indirect visits through work program reports to the madrasah head; an evaluation is carried out at the end of the school academic period by submitting a report on the overall madrasa library management program.